The Influence of Demographic Factors and Histopathological Variants in Survival Analysis of Malignant Minor Salivary Gland Tumors - Bokhari, Kamran (Journal of Orofacial Research, 2012)
Minor salivary gland tumors account for 2 to 4% of all head and neck cancers. These tumors are classically slow growing with patients being aware of their presence over months or even years. They are usually innocuous, asymptomatic and do not interfere with function till they attain large size. This retrospective study of malignant minor salivary gland tumors seen at Regional Cancer Center, Thiruvananthapuram, India over a period of 24 years included 84 cases. Aims: To assess the history, clinical presentation, pathological types of cases involving malignant minor salivary gland tumors and their influence on survival. Methods: The study was carried out in the division of surgical oncology, Regional Cancer Center, Thiruvananthapuram, India. A retrospective study design was adopted to assess the history, clinical presentation, pathological types. The cases were extracted from the electronic database by using International Classification of Diseases of Oncology (ICD-O) (Ist edition) codes of histology and sites. All patients were restaged using American Joint Committee on Cancer (AJCC) Tumor, Node and Metastasis (TNM) classification (2002). Demographic factors, clinical, histopathological findings were displayed with frequency tables. Survival was estimated by Kaplan-Meier method (Kaplan EL, Meier P: Nonparametric estimation from incomplete observations. J Amer Statist Assn 1958;53:457-81). Results: Mucoepidermoid carcinoma was the most common histopathological variant followed by adenoid cystic carcinoma. Mean age of the patients was 46.7 years. The overall disease free survival observed at 2 and 5 years in the present study was 73.3 and 59.7% respectively. Conclusion: The histological type of minor salivary gland tumor was found to significantly influence survival. Gender and habits had no significant influence on survival.